Stereocontrolled C(sp3)–P bond formation with non-activated alkyl halides and tosylates. Issue 40 (8th May 2017) - Yang, Chu-Ting; Han, Jun; Liu, Jun; Li, Yi; Zhang, Fan; Gu, Mei; Hu, Sheng; Wang, Xiaolin
Abstract : The current work provides a general approach for making C–P bonds with stereocontrol from chiral secondary alcohols. Abstract : The C(sp 3 )–P bond is formed via the reaction between P–H compounds and non-activated alkyl electrophiles, especially secondary alkyl halides and tosylates. This reaction proceeds via an SN 2 mechanism with inversion of configuration, so it can be used to form C–P bonds with stereocontrol from chiral secondary alcohols.